Integration of the Values of Surah Yunus Verse 57 in Guidance and Counseling Practice - Fatheni Cova Kamil Khairy; Hasan Zaini; Irmman (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2026)
Guidance and counseling practices are comprehensively designed to optimize individual’s ability to cope with challenges. The Islamic approach is a holistic approach one that integrates emotional and spiritual aspects. The objective of this study is to examine the concept of values ​​in Surah Yunus verse 57 as the foundation of Islamic guidance and counseling and analyze the integration of these values ​​in guidance and counseling practices. The method used in this study is a literature review. The results of the study indicate that the content of Surah Yunus verse 57 affirms that there are four functions of the Qur'an: teaching, healing (medicine), guidance, and mercy. These four aspects form the primary foundation of Islamic counseling practices, which encompasses the provisio of advice, the healing of spiritual ailments, guidance toward truth, and a approach characterized by compassion.